2015
DOI: 10.1038/ncomms8614
|View full text |Cite
|
Sign up to set email alerts
|

Local destruction of superconductivity by non-magnetic impurities in mesoscopic iron-based superconductors

Abstract: The determination of the pairing symmetry is one of the most crucial issues for the iron-based superconductors, for which various scenarios are discussed controversially. Non-magnetic impurity substitution is one of the most promising approaches to address the issue, because the pair-breaking mechanism from the non-magnetic impurities should be different for various models. Previous substitution experiments demonstrated that the non-magnetic zinc can suppress the superconductivity of various iron-based superco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
(78 reference statements)
2
23
0
Order By: Relevance
“…For the sake of convenience, we choose the proper local band parameters to make the valence of Zn close to 1. With this assumption, we are able to account for the suppressions of SC by Zn impurities in both electron-and hole-doped BaFe 2 As 2 with and without the SDW order as measured by experiments [14][15][16] using the same set of local band parameters.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For the sake of convenience, we choose the proper local band parameters to make the valence of Zn close to 1. With this assumption, we are able to account for the suppressions of SC by Zn impurities in both electron-and hole-doped BaFe 2 As 2 with and without the SDW order as measured by experiments [14][15][16] using the same set of local band parameters.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…First, we focus on single substituted-Zn ion at the center of lattice site I m = (14,14) at two different doping levels: n = 1.90 and n = 2.05. Fig.…”
Section: Superconductivity Suppression With the Increase Of Zinc Imentioning
confidence: 99%
See 2 more Smart Citations
“…For the ordinary SC wire supplemented with impurities we also concentrate our discussion on representative points in the nontopological parameter (phase) space. We keep the time-reversal invariant bulk superconductor unchanged by setting D = D = 0.1, although it has also been reported that impurities may suppress or even destroy superconductivity locally [71][72][73][74]. For the ordinary SC we have V Z =0 but in order to introduce magnetic impurities we set 1 V 0 Z , and the energy of these in-gap states may be tuned close to zero by varyingṼ Z .…”
Section: Transient Signature Of the Mzmmentioning
confidence: 99%